Duodenal perforation due to an ingested lollipop stick in a 7-year-old boy - Jinyoung Park (Journal of Pediatric Surgery Case Reports, 2019)
Ingestion of a foreign body is a frequently encountered clinical problem in children. Most swallowed foreign bodies are spontaneously excreted in the feces without intervention. Fewer than 1% of ingested foreign bodies lead to bleeding, obstruction or perforation of the gastrointestinal tract, mandating surgical intervention. This study describes a 7-year-old boy who presented with duodenal perforation caused by ingestion of a lollipop stick and who was successfully managed by surgery. Keywords: Foreign body, Lollipop stick, Duodenal perforation